Eksistensi Ragam Inlis dalam Komunikasi Digital di Threads: an Instagram App - Nicky Rosadi (Neolectura, 2023)
This study aims to reveal the existence of a variety of inlis in digital communication in the Threads: an Instagram app. The method used in this study is a qualitative method with descriptive analysis techniques. The object in this research is the conversation that occurs in Threads. The results of this study indicate that the existence of various inlis occurs and cannot be avoided. As with previous studies, the existence of this variety of inlis is always indicated by the use of short writing and the use of emoticons as a substitute for gestures. Based on the research that has been done, the writer concludes that the use of various inlis has become an option in conversations in cyberspace. For this reason, the authors suggest that people who socialize in cyberspace can better understand the use of this new variety in order to create harmonious communication and avoid miscommunication in cyberspace.